2015
DOI: 10.1016/j.bbamcr.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

8-Dehydrosterols induce membrane traffic and autophagy defects through V-ATPase dysfunction in Saccharomyces cerevisae

Abstract: 8-Dehydrosterols are present in a wide range of biologically relevant situations, from human rare diseases to amine fungicide-treated fungi and crops. However, the molecular bases of their toxicity are still obscure. We show here that 8-dehydrosterols, but not other sterols, affect yeast vacuole acidification through V-ATPases. Moreover, erg2Δ cells display reductions in proton pumping rates consistent with ion-transport uncoupling in vitro. Concomitantly, subunit Vph1p shows conformational changes in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 74 publications
2
11
0
Order By: Relevance
“…Vacuole vesicles extracted from cells treated with 3 μM tridemorph for 5 h were not capable to form proton gradients ( Figure 2A ). This impairment was similar using erg2Δ -derived vesicles ( Hernandez et al, 2015 ). Also in agreement with previous results, hydrolytic activity assays showed that V-ATPase activity was inhibited to a minor extent (435 ± 97 vs. 341 ± 8 μmol Pi min -1 mg -1 protein ± SEM for vesicles obtained from control and tridemorph-treated yeast cells respectively).…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…Vacuole vesicles extracted from cells treated with 3 μM tridemorph for 5 h were not capable to form proton gradients ( Figure 2A ). This impairment was similar using erg2Δ -derived vesicles ( Hernandez et al, 2015 ). Also in agreement with previous results, hydrolytic activity assays showed that V-ATPase activity was inhibited to a minor extent (435 ± 97 vs. 341 ± 8 μmol Pi min -1 mg -1 protein ± SEM for vesicles obtained from control and tridemorph-treated yeast cells respectively).…”
Section: Resultssupporting
confidence: 65%
“…In a previous report ( Hernandez et al, 2015 ), we described that the presence of 8-dehydrosterols in yeast membranes induced a change in subunit a of the V-ATPase that made it more susceptible to proteolytic attack. We hypothesized that limiting the proteolytic turnover of vacuolar proteins might help yeast to withstand tridemorph treatment.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Fungal resistance to DMIs can also be ascribed to overexpression of CYP51s, especially by some enhancer elements [9,[27][28][29][30][31][32][33]. In addition to CYP51s, recently, other genes encoding fungal ergosterol biosynthesis-related enzymes have been proposed to be potential targets, including ERG2 (encoding C − 8 sterol isomerase) [34][35][36] and ERG6 (encoding C − 24 sterol methyltransferase) [37][38][39][40]. The importance of both ERG2 and ERG6 to cycloheximide resistance for S. cerevisiae has also been genetically emphasized [41].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%